Effect of boundary conditions on progressive collapse resistance of RC beam-slab assemblies under edge column removal scenario. (15th December 2020) - Yu, Jun; Tang, Jian-hui; Luo, Li-zhong; Fang, Qin
Highlights: Resistance of RC beam-slab assemblies against progressive collapse are studied. Boundary conditions (BCs) affect assembly behavior only at large deformation stage. Resistance of assemblies only relies on concerned beams & slabs at strong BCs. Supporting column stiffness affects resistance of beam-slab assemblies at weak BCs. Free boundary beams with slab flange increase structural resistance at weak BCs. Abstract: Perimeter columns of building structures are the most susceptible to accidental loading (say, terrorist attacks or vehicle impact) due to their accessibility to the public, and thus progressive collapse is more likely caused by damage of perimeter columns. Previous studies show contrary or inconsistent conclusions of structural resistance form of RC beam-slab assemblies under an edge column removal scenario (CRS), probably because of inconsistent boundary restraints. Therefore, in this paper two specimens, each of which consisted of two square slab panels and seven beams, were experimentally investigated under a perimeter middle (PM) column removal scenario (CRS) and a penultimate exterior (PE) CRS, respectively, in which the former and the latter represent strong and weak boundary conditions in terms of lateral and rotational restraints to the assemblies in longitudinal direction. During the tests a static-determinate test-up was designed so that all the vertical reaction forces could be recorded. Through systematic instrumentation, progressive collapse resistance and load-transfer mechanisms of the assemblies are demonstrated, and the effects of boundary conditions are illustrated at the global behavior level and micro strain level. Thereafter, high-fidelity numerical models are built to evaluate the validity of the simplified boundary conditions in the tests and to investigate the effects of supporting column stiffness and restraint due to building continuity on progressive collapse resistance of PES. Finally, based on failure modes, analytical models to calculate the progressive resistance are derived using yield-line theory. The results indicate that structural resistance form of PES depends on the stiffness of supporting corner column, and adding slab flanges to the free boundary beam of PES is able to avoid torsional failure of boundary beams, as well as significantly increases structural resistance at large deformation stage.